Glutamine synthetase of Lotus corniculatus roots and nodules: characterisation and tissue-specific inhibition - Boxall, Jon Graham (1998)
Glutamine synthetase (GS), the enzyme responsible for the first step in the assimilation of ammonium in higher plants, generally exists in a number of isoforms associated with different tissues or cellular compartments within the plant. This study has investigated the GS isoenzyme composition of roots and N-fixing root nodules of the temperate legume, Lotus comiculatus, and has used a novel transgenic approach to manipulate the spatial distribution of the enzyme within these tissues.